Non-custodial deaths: missing, ignored or unimportant? - Phillips, Jake (Criminology & criminal justice, 2019)
This article presents the findings from two separate pieces of research that were conducted by the authors on deaths that occur within the criminal justice system, but outside custodial settings. The article begins with a review of the literature on deaths both within and outside custody before going through the research findings which inform the article. The overarching argument is that deaths outside custodial settings are less understood, and receive much less scrutiny and public attention than equivalent deaths that occur in custody. We explore the reasons for this neglect, drawing attention to policy, methodological and sociological factors. We conclude by reflecting on possible ways of overcoming this neglect by drawing on a body of work which argues in favour of an ethic of care.